Analytical model for circular high strength concrete filled steel tubes under compression. (1st October 2021) - Zhu, Jiong-Yi; Chen, Junbo; Chan, Tak-Ming
Highlights: The initiation of confinement in CFST is captured and modelled. A confinement-related analysis model of CFST is proposed. Reduction of confining pressure in CFST with high strength concrete is proposed. The proposed analysis model well predicts the axial and lateral stress–strain relationships of CFST. Abstract: It is well known that the effect of confinement in concrete filled steel tube (CFST) can enhance the axial compressive strength of the concrete core. The confining pressure is a key issue to determine the compressive strength of concrete while the development of confining pressure is related to the lateral responses of steel tube and concrete core. This paper firstly presents a review on the lateral behaviour of circular CFST and existing lateral-axial strain models for concrete. These models are assessed by the authors' previous experimental observations. Assessment results reveal deficiencies of current lateral-axial strain models, especially on the CFST with high strength concrete. A modified lateral-axial strain model for both normal and high strength concrete core in CFST was then proposed to accurately capture the interaction behaviour of the steel tube and the concrete. An analytical model of CFST with uniformly confined concrete core (i.e. with circular section) was then proposed to capture the development of confining pressure in CFST. A reduction factor was considered when the high strength concrete was used. The proposed analytical model can well predict the load bearing capacity, load-shortening curve, axial strain-lateral strain relationship of CFST with normal and high strength concrete.